National Library of Australia, exterior views of the new extensions, Canberra, 9 September 1986 - National Library of Australia. Photographic Section (1986)
Includes photographs of: Henry Moore's 1969 sculpture "Two piece reclining figure no. 9"; exterior of National Library of Australia; lower ground floor 1 extensions to the Library; parkland, fountain, roads and pathways surrounding the Library; interior of Map Reading Room; distant view of Commonwealth Avenue Bridge. (Photographs taken by a National Library of Australia staff photographer)
Condition: Good.
Selected images individually catalogued and digitised.
21 negatives in 2 packets (a and b) plus 4 contact sheets (negatives for 18 images on contact sheets 1 and 3 unavailable)
Title devised by cataloguer based on information supplied by photographer.
Keywords: Moore, Henry, -- 1898-1986.; National Library of Australia -- Buildings -- Photographs; Public sculpture -- Australian Capital Territory -- Canberra -- Photographs; Outdoor sculpture -- Australian Capital Territory -- Canberra -- Photographs; Canberra (A.C.T.) -- Buildings, structures, etc. -- Photographs